2011
DOI: 10.3109/00365599.2011.568954
|View full text |Cite
|
Sign up to set email alerts
|

Waldenström's macroglobulinemia and nephrotic syndrome with membranous nephropathy

Abstract: Renal complications of Waldenström's macroglobulinemia (WM) are rarely observed. Nephrotic syndrome in association with WM has most often been secondary to amyloidosis. This article reports a case of WM with nephrotic syndrome as a result of membranous nephropathy with immunoglobulin M (IgM) deposition. A 44-year-old male diagnosed with WM 4 years previously, presented with heavy proteinuria (7.8 g/24 h). Kidney biopsy revealed expanded mesangium, thickened capillary loops and epimembranous spikes, with no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Immunotactoid and fibrillary GN, cryo-GN, monoclonal immunoglobulin deposition disease, MPGN, MN, crescentic GN, MCD, and FSGS have also been described. 9,19,20,[24][25][26] ICMDD was found in 4 (36.3%) out of our 11 patients with WM; the rest presented with single cases of AL amyloidosis, cryo-GN, and monotypic MN. In addition, we observed a case of C3-GN.…”
Section: Discussionmentioning
confidence: 68%
“…Immunotactoid and fibrillary GN, cryo-GN, monoclonal immunoglobulin deposition disease, MPGN, MN, crescentic GN, MCD, and FSGS have also been described. 9,19,20,[24][25][26] ICMDD was found in 4 (36.3%) out of our 11 patients with WM; the rest presented with single cases of AL amyloidosis, cryo-GN, and monotypic MN. In addition, we observed a case of C3-GN.…”
Section: Discussionmentioning
confidence: 68%
“…To the best of our knowledge, our present patient is the first patient to date showing MGRS presenting as MN with IgM-type monoclonal deposition. Although rare, there have been a number of reported cases of patients with MN showing dominant IgM deposition ( 16 , 17 ). Among them, there has been a case of a patient with IgM lambda-type MN accompanied with Waldenström macroglobulinemia (WM), who was treated effectively with rituximab and fludarabine.…”
Section: Discussionmentioning
confidence: 99%
“…8 The authors found only 13 cases of leukemia and 10 cases of lymphoma and membranous nephropathy reported. Since then, the current authors performed a similar PubMed search with criteria "lymphoma," "leukemia," "Waldenstrom," and "membranous nephropathy" published since 2006 and identified 7 additional cases associated with chronic lymphocytic leukemia, [16][17][18][19] one case associated with Waldenstrom's macroglobulinemia, 9 and 10 additional cases associated with lymphoma, predominantly non-Hodgkin's lymphoma. [20][21][22][23][24][25][26][27][28] In paraneoplastic membranous nephropathy, only 10% of patients were diagnosed with cancer before their diagnosis of membranous nephropathy.…”
Section: Paraneoplastic Glomerulonephritismentioning
confidence: 99%
“…3 However, a small number of case reports do exist for hematologic disorders such as chronic lymphocytic leukemia and Waldenstrom's macroglobulinemia. [7][8][9] With time, we have also identified more associations with secondary nephropathy in the setting of malignancy to include therapeutics for malignancy and in the setting of graft versus host disease in patients posthematopoietic stem cell transplant, which is often done for a bone marrow malignancy. [10][11][12][13][14][15] And, finally some patients with malignancy may have membranous nephropathy unrelated to their malignancy or therapy and be diagnosed with idiopathic primary membranous nephropathy.…”
Section: Introductionmentioning
confidence: 99%